Interrogation or Experimentation? Assessing Non-Consensual Human Experimentation During the War on Terror - Aceves, William J. (2018)
The prohibition against non-consensual human experimentation has long been considered sacrosanct. It traces its legal roots to the Nuremberg trials although the ethical foundations dig much deeper. It prohibits all forms of medical and scientific experimentation on non-consenting individuals. The prohibition against non-consensual human experimentation is now well established in both national and international law. Despite its status as a fundamental and non-derogable norm, the prohibition against non-consensual human experimentation was called into question during the War on Terror by the CIA’s treatment of “high-value detainees.” Seeking to acquire actionable intelligence, the CIA tested the “theory of learned helplessness” on these detainees by subjecting them to a series of enhanced interrogation techniques. This Article revisits the prohibition against non-consensual human experimentation to determine whether the CIA’s treatment of detainees violated international law. It examines the historical record that gave rise to the prohibition and its eventual codification in international law. It then considers the application of this norm to the CIA’s treatment of high-value detainees by examining Salim v. Mitchell , a lawsuit brought by detainees who were subjected to enhanced interrogation techniques. This Article concludes that the CIA breached the prohibition against non-consensual human experimentation when it conducted systematic studies on these detainees to validate the theory of learned helplessness